Human Resource Management of Teachers at Madrasah Aliyah Pesantren: An Education Quality Perspective - B Baso; Rusdi Rasyid; Sain Hanafy (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2018)
This paper discusses human resource management from an education quality perspective. This study aims to find out the description of human resources in building the quality of education. This study applies descriptive qualitative. Data source from Madrasah principals, heads of administration, head of curriculum and evaluation, and educators. Data collection method by interviewing the participants. The instrument of this study uses interview guidelines. Data analysis were carried out through three stages, namely data reduction, data presentation, and conclusion. The results showed that human resources in the Madrasah Aliyah IMMIM Makassar Modern Islamic Boarding School were in the good category. The reality of the quality of education shows very satisfying results, it is categorized in very good. The implication of this study is that it is hoped that it can become information and reference about the need to review the activities of human resource management in developing the quality of education, primarily from the perspective of internal customers consisting of educators and education personnel as